Telomeric ORFs (TLOs) in Candida spp. Encode mediator subunits that regulate distinct virulence traits. - HARAN, JOHN; FLEMING, ALASTAIR; HOKAMP, KARSTEN (My University, 2014)
The TLO genes are a family of telomere-associated ORFs in the fungal pathogens Candida albicans and C. dubliniensis that encode a subunit of the Mediator complex with homology to Med2. The more virulent pathogen C. albicans has 15 copies of the gene whereas the less pathogenic species C. dubliniensis has only two ( CdTLO1 and CdTLO2 ). In this study we used C. dubliniensis as a model to investigate the role of TLO genes in regulating virulence and also to determine whether TLO paralogs have evolved to regulate distinct functions. A C. dubliniensis tlo1 D / tlo2 D mutant is unable to form true hyphae, has longer doubling times in galactose broth, is more susceptible to oxidative stress and forms increased levels of biofilm. Transcript profiling of the tlo1 D / tlo2 D mutant revealed increased expression of starvation responses in rich medium and retarded expression of hypha-induced transcripts in serum. ChIP studies indicated that Tlo1 binds to many ORFs including genes that exhibit high and low expression levels under the conditions analyzed. The altered expression of these genes in the tlo1 D / tlo2 D null mutant indicates roles for Tlo proteins in transcriptional activation and repression. Complementation of the tlo1 D / tlo2 D mutant with TLO1 , but not TLO2 , restored wild-type filamentous growth, whereas only TLO2 fully suppressed biofilm growth. Complementation with TLO1 also had a greater effect on doubling times in galactose broth. The different abilities of TLO1 and TLO2 to restore wild-type functions was supported by transcript profiling studies that showed that only TLO1 restored expression of hypha-specific genes ( UME6, SOD5 ) and galactose utilisation genes ( GAL1 and GAL10 ), whereas TLO2 restored repression of starvation-induced gene transcription. Thus, Tlo/Med2 paralogs encoding Mediator subunits regulate different virulence properties in Candida spp. and their expansion may account for the increased adaptability of C. albicans relative to other Candida species
PUBLISHED
Keywords: Candida albicans; Candida albicans; Genes & Society; Immunology, Inflammation & Infection; Genomes, Genomics; Microbiology; Molecular Biology